2007
DOI: 10.1177/0009922806298647
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions About Influenza Vaccination Among Parents of Healthy Young Children

Abstract: A survey was administered to 828 parents from metropolitan Denver, Colorado, and 57% responded. Of the respondents, 47% thought their child was unlikely to contract influenza, 70% thought influenza vaccine could cause influenza, and 21% considered influenza vaccination unsafe for a 1-year-old child. The influenza immunization rate in children of surveyed parents was 71%. In multivariate analyses, the perception that influenza vaccination was the social norm was positively associated with immunization (odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 33 publications
5
90
2
Order By: Relevance
“…The decrease in vaccine coverage rate of whole cell pertussis vaccine in Japan due to concerns about encephalopathy, low MMR acceptance rates due to rumors about autism, and low uptake of hepatitis B vaccines containing thiomersal are well-known examples, some of which even led to outbreaks [15,20,23,27]. The same association between parental fears and low uptake of seasonal inluenza vaccine is also shown [1,8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The decrease in vaccine coverage rate of whole cell pertussis vaccine in Japan due to concerns about encephalopathy, low MMR acceptance rates due to rumors about autism, and low uptake of hepatitis B vaccines containing thiomersal are well-known examples, some of which even led to outbreaks [15,20,23,27]. The same association between parental fears and low uptake of seasonal inluenza vaccine is also shown [1,8].…”
Section: Discussionmentioning
confidence: 98%
“…Many of them searched intention to get the vaccine before vaccines were available and found that perception of the public about the severity of the pandemic or the disease, the cultural characteristics of eastern and western societies, different media coverages of pandemic vaccines according to political leanings of media groups, concerns about vaccine safety, health provider characteristics, or not receiving seasonal influenza vaccine had an effect on low vaccine coverage rates [10,18,26]. Most of those studies also emphasized that whether intention to get the vaccine would translate to behavior was not known then [8]. Recently, a limited number of studies have been published on parental attitudes towards pandemic vaccines when the vaccines were readily available [25,37].…”
Section: Introductionmentioning
confidence: 99%
“…Families declare that "too much vaccination" is performed on their children, that these cause the immune system to attenuate and influenza vaccine even "causes" the disease itself (25). In adult diabetics, fear of adverse-effects is among the least common reasons but it increases to be more common in children (29)(30)(31). The rates of fear of adverse-effects are between 8.9-18.8% in different studies (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…25 Questions were adapted from existing surveys assessing related concepts because previous questionnaires did not assess attitudes and beliefs toward 2009 H1N1 influenza. [26][27][28][29] Measures. Vaccination uptake.…”
mentioning
confidence: 99%